Logo rebranding: Indonesian tax authority public relations strategy in forming organizational culture images - Febri Noviardi; Andre Noevi Rahmanto; Yulius Slamet (Universitas Negeri Yogyakarta, 2020)
This paper explains how the process of rebranding the logo of the Directorate General of Taxes (DGT) of the Republic of Indonesia carried out by DGT public relations in shaping the image by displaying the cultural values of the Ministry of Finance. This is motivated by the lack of a comprehensive explanation of the process of rebranding the logo in previous studies. At DGT, logo rebranding is carried out because of the low level of the public’s trust in the DGT. Therefore, one of the strategies of the DGT public relations is the formation of an institutional image. This study uses a research method with a qualitative approach with data collection conducted by interviewing selected informants using purposive sampling techniques and source triangulation as a technique in testing the validity of the data. The results are analyzed using the Assessment, Communication and Analysis, Design, and Action planning model. The rebranding process was 1) describing the problem, 2) using all channels communication and objectives in delivering a new logo, 3) using professional consultants in planning that consist of research, strategy development, and implementation, 4) as well as carrying out plans, setting rules, and supervising all activities in the DGT’s rebranding process.Tulisan ini menjelaskan bagaimana proses rebranding logo Direktorat Jenderal Pajak (DJP) RI yang dilakukan oleh Humas DJP dalam membentuk citra dengan menampilkan nilainilai budaya organisasi Kemenkeu. Hal ini dilatarbelakangi oleh kurangnya penjelasan yang komprehensif terhadap proses rebranding logo pada studi-studi sebelumnya. Pada DJP, rebranding logo dilakukan karena rendahnya tingkat kepercayaan masyarakat terhadap DJP. Oleh karena itu, salah satu strategi Public Relations (PR) adalah dengan pembentukan citra institusi. Penelitian ini menggunakan metode penelitian dengan pendekatan kualitatif dengan pengumpulan data dilakukan dengan cara wawancara kepada informan terpilih menggunakan teknik purposive sampling dan triangulasi sumber sebagai teknik dalam uji keabsahan datanya. Hasilnya dianalisis menggunakan model perencanaan Assessment, Communication and Analysis, Design, dan Action. Proses rebranding yang dilakukan yaitu 1) menggambarkan masalah, 2) menggunakan semua saluran komunikasi dan tujuan dalam memberikan logo baru, 3) menggunakan konsultan profesional dalam perencanaan yang terdiri dari penelitian, pengembangan strategi, dan implementasi, 4) serta melaksanakan perencanaan, menetapkan aturan, dan melakukan pengawasan terhadap seluruh kegiatan pada proses rebranding Ditjen Pajak RI.